Planning additions to academic library buildings : a seamless approach - Hawthorne, Pat; Martin, Ron G. (American Library Association, 1995)
The "seamless approach" is the best strategy for planning additions to existing academic library buildings. Additions to existing library buildings are becoming a fact of life at many colleges and universities. Space considerations, the need for proximity to existing space, and the desire for a unified appearance usually preclude designing a totally new structure in many cases. So adding on to existing space is not only the best option for many academic libraries; it's the only one. The Catch-22 is that there is usually little to be gained by attempting to impose a too-modern structure on existing buildings. The solution is a seamless approach that incorporates and enhances the features of existing structures. The result is usually a functional and appealing addition, rather than a design that meets space needs but looks like an afterthought